Development job sheet brake system practice for learning automotive vehicle engineering student in vocational education - Prakoso, Habib Ramdhan; Purnomo, Sigit; Subagyo, Subagyo; Efendi, Adhan; Susetyo , Eko; Samidjo, Samidjo (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to (1) design and develop teaching materials namely job sheet disc brake system practice, (2) Obtain the feasibility level of teaching material products, namelyjob sheet brake system practice. This research will use the so-called development method Reseach and Development (R&D) was carried out on Vocational Education Automotive Vehicle Engineering students. The instrument of this data collector will use a questionnaire or commonly called a questionnaire distributed to media experts and material experts, as well as 8 small group test students and 25 field test students. The results of the validation trial by material experts get a percentage of 91.9% which can be categorized as valid. Meanwhile, from media experts, a percentage of 92.7% can be categorized as valid. Assessment by students of the Department of Automotive Light Vehicle Engineering vocational education obtained a percentage of 85.5% categorized as valid, therefore, this assessment can be interpreted if job sheet the practice of the disc brake system is very appropriate to be used as a learning resource for vocational education students of the Department of Automotive Vehicle Engineering.